2012
DOI: 10.1007/s10165-012-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the affected joints in rheumatoid arthritis patients in a large Japanese cohort

Abstract: Based on the results of this study, we can draw the following conclusions: (1) the wrist was the most affected joint; (2) there was a discrepancy between the distribution of swollen joints and that of tender joints; and (3) the distribution of affected joints was uniform regardless of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…However, the main limitation of our study lies in the 11 (27%) countries where only one rheumatologist participated. Referent studies from Switzerland (mean age of RAO 51.5 years) [49], Japan (49 years) [50], Kenya (41 ± 17 years) [51], Nigeria (42 years) [52], Sweden (58 ± 18 years) [14], Russia (53 years) [53], Colombia (44 ± 12 years) [54], Burkina Faso (35 years) [55], and Iran (41 ± 13 years) [56] reported figures similar to ours. We did not find referent studies from Ghana or Panama.…”
Section: Discussionsupporting
confidence: 86%
“…However, the main limitation of our study lies in the 11 (27%) countries where only one rheumatologist participated. Referent studies from Switzerland (mean age of RAO 51.5 years) [49], Japan (49 years) [50], Kenya (41 ± 17 years) [51], Nigeria (42 years) [52], Sweden (58 ± 18 years) [14], Russia (53 years) [53], Colombia (44 ± 12 years) [54], Burkina Faso (35 years) [55], and Iran (41 ± 13 years) [56] reported figures similar to ours. We did not find referent studies from Ghana or Panama.…”
Section: Discussionsupporting
confidence: 86%
“…This was the first study that explored the relationship between the initially affected joint and the final diagnosis. Kanazawa et al . indicated that the wrist was the most frequently affected site in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first study that explored the relationship between the initially affected joint and the final diagnosis. Kanazawa et al 19 indicated that the wrist was the most frequently affected site in RA patients. This finding is in accordance with the present study, which demonstrated that wrist joint involvement is a predictor of monoarticular RA.…”
Section: Figurementioning
confidence: 99%
“…Although patients were generally not evaluated at the time of diagnosis, the scarcity of available evidence suggests differences in RA phenotype in various populations. 13 14 Therefore, we studied the distribution of joint inflammation at the time of diagnosis in different RA populations (Mexican, Dutch, Indian and South African). In addition, within the Indian and Dutch populations, the joint distribution was subsequently compared between autoantibody-positive and negative patients with RA.…”
Section: Introductionmentioning
confidence: 99%